1990
DOI: 10.1128/jvi.64.10.5093-5105.1990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 68-kilodalton nuclear ATP-binding phosphoprotein encoded by bovine papillomavirus type 1

Abstract: El is the largest open reading frame (ORF) of bovine papillomavirus type 1 (BPV-1) and is highly conserved among all papillomaviruses, maintaining its size, amino acid composition, and location in the viral genome with respect to other early genes. Multiple viral replication functions have been mapped to the El ORF of BPV-1, and evidence suggested that more than one protein was encoded by this ORF. We previously identified a small protein (M) whose gene consists of two exons, one encoded by the 5' end of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…Amino acid similarities suggested that El, like SV40 large-T antigen, may be a DNA helicase/ATPase involved in initiating viral DNA replication (3). Subsequently, BPV-1 El protein was shown to be a nuclear 68-72 kD ATP-binding phosphoprotein (4,5,6). A mutation in El (Pro-434 to Ser), analogous to that in the SV40 large-T antigen mutant tsA209 that impairs ATPbinding, renders BPV-1 defective for DNA replication and abolishes ATP-binding by El (6).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid similarities suggested that El, like SV40 large-T antigen, may be a DNA helicase/ATPase involved in initiating viral DNA replication (3). Subsequently, BPV-1 El protein was shown to be a nuclear 68-72 kD ATP-binding phosphoprotein (4,5,6). A mutation in El (Pro-434 to Ser), analogous to that in the SV40 large-T antigen mutant tsA209 that impairs ATPbinding, renders BPV-1 defective for DNA replication and abolishes ATP-binding by El (6).…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear-localised early protein E l shares some biochemical characteristics with SV40 large T antigen, including helicase and ATPase activities (Clertant and Seif, 1984;Sun et al, 1990). The SV40 large T antigen is the only viral protein required for SV40 replication (Myers and Tjian, 1980) and the functions of the E l protein are consistent with it performing a similar role.…”
mentioning
confidence: 98%
“…It is therefore likely that the differences between SV40 and BPV1 lie with the proteins involved in the initiation of replication. The E1 protein, which shares a number of biochemical properties with the T antigen, has been clearly established as the initiator of BPV1 replication (33,35,36,43,52). The role of the E2 transactivator protein in BPV1 replication is less clear.…”
mentioning
confidence: 99%